2007
DOI: 10.1097/01.brs.0000250304.24001.24
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Multisegment Anterior Cervical Fixation Using Bone Strut Graft Versus a Titanium Rod and Buttress Prosthesis

Abstract: A titanium rod and buttress prosthesis may be a faster and easier alternative to conventional iliac crest/fibula autograft after multisegmental cervical vertebral corpectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 41 publications
0
21
0
2
Order By: Relevance
“…Several reviews of literature documented the challenge with anterior multilevel fusions [3,10,31,32]. Reports of failure with anterior-only instrumentation of 2-and even 1-level corpectomies continue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reviews of literature documented the challenge with anterior multilevel fusions [3,10,31,32]. Reports of failure with anterior-only instrumentation of 2-and even 1-level corpectomies continue.…”
Section: Discussionmentioning
confidence: 99%
“…With anterior procedures, decompression of the neurologic structures can be accomplished by means of segmental discectomy or partial corpectomy. With the number of decompressed levels, particularly corpectomies performed, the intrinsic stability of the spine drops, which is a challenge to current anterior instrumentations [10]. Likewise, two reviews of literature identified a high rate of complications in reconstructive multilevel ([2 levels) cervical spine surgery, particularly if decompression required multiple corpectomies and a posterior supplemental instrumentation was not performed [3,31].…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies have been performed using either an allograft or autograft (Table 1). Other contemporary methods used for reconstruction include artificial disc, PEEK cages, carbon fiber cages, and titanium rods with buttress prosthesis [5]. The cervical artificial disc has been recently approved by the United States Food and Drug Administration (FDA) and is still not widely used [27].…”
Section: Groupmentioning
confidence: 99%
“…Notably, complications in reconstructive multilevel (C2 levels) cervical spine surgery are frequent, particularly if decompression requires multiple corpectomies in biomechanically challenging settings and if a posterior supplemental instrumentation is not performed [2,[11][12][13][14]. In a review of literature, the rate of nonunions in multilevel ACDF and failure rates for long-length cervical decompressions/corpectomies with multilevel fusion has been observed as high as 15-50 % and up to 30-75 %, respectively.…”
Section: Introductionmentioning
confidence: 99%